Two new species of Trigonidiidae (Orthoptera: Grylloidea) from southwest China - Yuan, Wei; Wu, Jiawei; Ma, Li-Bin; Gu, Jun-Jie (Zootaxa, 2025)
Two new species of Trigonidiinae (Orthoptera: Grylloidea; Trigonidiidae), Trigonidium albarum sp. nov. and Svistella prominens sp. nov., were discovered in Sichuan Province, China. T. albarum sp. nov. has a similar coloration to Trigonidium rubrumoculum He & Ma, 2022 and can be distinguished by different ectoparamere; while S. prominens sp. nov. and Svistella anhuiensis He, Li & Liu, 2009 have similar morphological characteristics and are distributed in the same area, but the new species is characterized by a dark yellow body and a semicircular protrusion on the lateral lobe of epiphallus. This article presents descriptions and illustrations of the new species.